Stanisław Staszic. Między Bogiem a naturą - Skodlarski, Janusz (Annales. Etyka w Życiu Gospodarczym, 2015)
From a very young age till the last days of his life, Stanisław Staszic was occupied by the question of the relationship between God and Nature. In particular, the Polish thinker was interested in the vision of the world in which human life and Nature were seen in unison, in accordance with laws of reason and the outcomes of scientific investigations. His deliberations on Nature validated his monistic worldview, encompassed within a deistic general framework. Staszic pointed out many times that natural order is the creation of God, however, earthly issues are in the hands of humans. In the last years of his life he withdrew from God. He did not accept the Church’s hierarchy, while his approach to the Creator was ambivalent.